Stability Studies of Selected Metal Ions Chelates with 2-(4-amino-1,5- dimethyl-2-phenyl-1,2-dihydro-pyrazol-3-ylideneamino) Phenol - Gouda, Gamal A.; Ali, Gomaa A. M.; Elnasr, Tarek A. Seaf (Natural Sciences Publishing Cor., 2015)
Acid dissociation and complex stability constants of 2-(4-Amino-1,5-dimethyl-2-phenyl-1,2-dihydro-pyrazol-3- ylideneamino) phenol (H2A) with some metal ions chelates have been determined potentiometrically using 0.1 M KCl and 20 % (v/v) ethanol-water mixture. The stability constants of the formed complexes were found to be in the order Re5+ > Ce3+ > Pd2+ >Th4+ > Hg2+ > Co2+. The dissociation constants (pKa) of H2A and the stability constants (log Ki) of their complexes were determined at 298, 308 and 318 K. The corresponding thermodynamic parameters (ΔG, ΔH and ΔS) were calculated and discussed. The results indicated that, the dissociation process is non-spontaneous, endothermic and entropically unfavorable. The formation of the metal complexes has been found to be endothermic and entropically favorable